PENGUATAN MANAJEMEN PEMASARAN SYARIAH BERBASIS DIGITAL - Alto Wirahadi Kusuma; Isfandayani Isfandayani; Purnama Putra; Fajri Ryan Isnandar; Rizal Fahlevi (LPPM Universitas Islam 45, 2023)
The purpose of this service is to help and overcome the problems faced related to the less than optimal marketing management of the PAUD Qur'an Sabilussomad institution in Lubang Buaya Village. The solution offered to the PAUD Qur'an Sabilussomad institution by optimizing digital-based sharia marketing management via social media instagram and whatsApp. The implementation method used in helping and overcoming the problems encountered via several real lecture programs, namely first, socialization and education of digital-based sharia marketing management concepts. Second, training in making marketing strategies and flyer designs. Lastly, assistance in digital-based sharia marketing activities via social media instagram and whatsapp. The results of the implementation of service to partners are first, partners can understand the concept of digital-based sharia marketing management. Second, partners can create marketing strategies and design flyers. Finally, partners can implement digital-based sharia marketing activities via social media instagram and whatsapp.